Ant Species Richness and Diversity in Selected Habitats in Chavara Panchayath, Kollam District, Kerala, India - Krishnan, Arya; D., Dhanyaraj; P., Kiran (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ants are an important part of the ecosystem not only because of their huge biomass but also because of their role in the ecosystem. The aim of this study is to address the diversity and abundance of ants in Chavara panchayat, Kollam district, Kerala. The study records a total of 16 ant species belongs to 1 family, 7 tribes, and 3 subfamilies in Chavara panchayat, which provides a brief scenario and improves our knowledge the diversity and distribution of the myrmecofauna in the region. The subfamilies include Formicinae (4 genera and 7 species), Myrmicinae (5 genera and 6 species), and Ponerinae (3 genera and 3 species). Formicinae was the most diverse subfamily, Myrmicinae was the most abundant tribe, and Ponerinae was the least abundant and most diverse subfamily. Biodiversity indices show that the study area has high biodiversity and species richness.